Revisiting the EKC Hypothesis With Export Diversification and Ecological Footprint Pressure Index for India: A RALS-Fourier Cointegration Test - Pata, UK; Shahzad, Farrukh; Fareed, Zeeshan; Rehman, MA (Frontiers in Environmental Science, 2022)
This study assesses India's environmental problems by focusing on the ecological footprint pressure index (EFPI), which provides a simultaneous analysis of biocapacity and ecological footprint. In particular, the study examines the impact of export diversification, economic growth, and renewable energy on EFPI under the environmental Kuznets curve (EKC) hypothesis for India. To analyze the long-run relationships, the Residual Augmented Ordinary Least Squares (RALS)-Fourier cointegration test is applied to annual data from 1965 to 2014. Contrary to the EKC hypothesis, the results show a U-shaped relationship between income and EFPI. The absence of the EKC hypothesis implies that economic development does not help to ensure environmental quality; hence, other measures are required to minimize irreversible environmental problems. In this regard, the results of the study suggest that renewable energy consumption and export diversification reduce EFPI. Based on the overall findings of the study, it is recommended that the Indian government improve environmental values by changing the export structure and energy mix.